2015
DOI: 10.1038/srep14237
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Identifies Frequent Somatic Mutations in Cell-Cell Adhesion Genes in Chinese Patients with Lung Squamous Cell Carcinoma

Abstract: Lung squamous cell carcinoma (SQCC) accounts for about 30% of all lung cancer cases. Understanding of mutational landscape for this subtype of lung cancer in Chinese patients is currently limited. We performed whole exome sequencing in samples from 100 patients with lung SQCCs to search for somatic mutations and the subsequent target capture sequencing in another 98 samples for validation. We identified 20 significantly mutated genes, including TP53, CDH10, NFE2L2 and PTEN. Pathways with frequently mutated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 51 publications
6
37
0
Order By: Relevance
“…In addition, Biankin et al found aberrations in axon guidance pathway genes in pancreatic cancer genomes. Furthermore, mutations in CDH10 were identified in colorectal cancer and lung cancer recently . These findings are in line with our studies that variations in CDH10 coding or nearby genomic regions may play roles in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, Biankin et al found aberrations in axon guidance pathway genes in pancreatic cancer genomes. Furthermore, mutations in CDH10 were identified in colorectal cancer and lung cancer recently . These findings are in line with our studies that variations in CDH10 coding or nearby genomic regions may play roles in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, mutations in CDH10 were identified in colorectal cancer and lung cancer recently. [20][21][22] These findings are in line with our studies that variations in CDH10 coding or nearby genomic regions may play roles in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…26,27 It has also been reported that, in lung squamous cancer cells, the knockdown of CDH10 promotes cell proliferation, soft agar colony formation, cell migration, and cell invasion, whereas the overexpression of CDH10 inhibits cell proliferation. 28 CDH10 was found to be frequently mutated in both lung squamous cell carcinoma and adenocarcinoma, which indicates the importance of CDH10 mutations in the development of nonYsmall cell lung cancer. 29 Taken together, we postulate that mutant CDH10 may play important roles, or at least partial roles, in the invasion and metastasis of EC.…”
Section: Discussionmentioning
confidence: 95%